Morphologies and dynamics of linear ABC triblock copolymers with different block sequences1. Issue 10 (6th February 2015) - Zhou, Yang; Long, Xinping; Xue, Xianggui; Qian, Wen; Zhang, Chaoyang
<x xml:space="preserve">Abstract</x> Two different mechanisms of dynamic evolution, i.e. "contacting and fusing" for l-ABC and l-ACB, and "folding and fusing" for l-BAC, are founded firstly.